Unwelcome Refugees: Steppe Migrants in the Byzantine Balkans (11th–12th c.) - Paroń, Aleksander (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
This study is an attempt to answer two questions: how did Byzantium cope with steppe refugees, and how did the experience of their presence influence later (until the end of the 12th century) relations of the empire with the inhabitants of the Black Sea steppes.